The Structural and Functional Correlates of Frailty in Persons With Human Immunodeficiency Virus. (11th April 2022) - Strain, Jeremy F; Cooley, Sarah; Kilgore, Collin; Nelson, Brittany; Doyle, John; Thompson, Regina; Westerhaus, Elizabeth; Petersen, Kalen J; Wisch, Julie; Ances, Beau M
Abstract: Background: Persons with HIV (PWH) are at increased risk of frailty, a clinically recognizable state of increased vulnerability resulting from aging-associated decline in multiple physiologic systems. Frailty is often defined by the Fried criteria, which includes subjective and objective standards concerning health resiliency. However, these frailty metrics do not incorporate cognitive performance or neuroimaging measures. Methods: We compared structural (diffusion tensor imaging [DTI]) and functional (cerebral blood flow [CBF]) neuroimaging markers in PWH with frailty and cognitive performance. Virologically controlled PWH were dichotomized as either frail (≥3) or nonfrail (<3) using the Fried criteria. Cognitive Z -scores, both domain (executive, psychomotor speed, language, and memory) and global, were derived from a battery of tests. We identified three regions of reduced CBF, based on a voxel-wise comparison of frail PWH compared with nonfrail PWH. These clusters (bilateral frontal and posterior cingulate) were subsequently used as seed regions of interest (ROIs) for DTI probabilistic white matter tractography. Results: White matter integrity connecting the ROIs was significantly decreased in frail compared with nonfrail PWH. No differences in cognition were observed between frail and nonfrail PWH. However, reductions in white matter integrity among these ROIs was significantly associated with worse psychomotor speed and executive function across the entire cohort. Conclusions: We conclude that frailty in PWH can lead to structural and functional brain changes, including subtle changes that are not detectable by standard neuropsychological tests. Multimodal neuroimaging in conjunction with frailty assessment could identify pathological brain changes observed in PWH. Abstract : Increased susceptibility to brain structural and functional damage was observed in individuals with both human immunodeficiency virus (HIV) and frailty compared with individuals with HIV and without frailty. Therefore, imaging metrics may have clinical utility for monitoring individuals with both HIV and frailty.